CRISPR-Cas9-mediated deletions of FvMYB46 in Fragaria vesca reveal its role in regulation of fruit set and phenylpropanoid biosynthesis - Arti Rai; Magne Nordang Skårn; Abdelhameed Elameen; Torstein Tengs; Mathias Rudolf Amundsen; Oskar S. Bjorå; Lisa K. Haugland; Igor A. Yakovlev; May Bente Brurberg; Tage Thorstensen (BMC Plant Biology, 2025)
Abstract The phenylpropanoid pathway, regulated by transcription factors of the MYB family, produces secondary metabolites that play important roles in fertilization and early phase of fruit development. The MYB46 transcription factor is a key regulator of secondary cell wall structure, lignin and flavonoid biosynthesis in many plants, but little is known about its activity in flowers and berries in F. vesca. For functional analysis of FvMYB46, we designed a CRISPR-Cas9 construct with an endogenous F. vesca-specific U6 promoter for efficient and specific expression of two gRNAs targeting the first exon of FvMYB46. This generated mutants with an in-frame 81-bp deletion of the first conserved MYB domain or an out-of-frame 82-bp deletion potentially knocking out gene function. In both types of mutant plants, pollen germination and fruit set were significantly reduced compared to wild type. Transcriptomic analysis of flowers revealed that FvMYB46 positively regulates the expression of genes involved in processes like xylan biosynthesis and metabolism, homeostasis of reactive oxygen species (ROS) and the phenylpropanoid pathway, including secondary cell wall biosynthesis and flavonoid biosynthesis. Genes regulating carbohydrate metabolism and signalling were also deregulated, suggesting that FvMYB46 might regulate the crosstalk between carbohydrate metabolism and phenylpropanoid biosynthesis. In the FvMYB46-mutant flowers, the flavanol and flavan-3-ol contents, especially epicatechin, quercetin-glucoside and kaempferol-3-coumaroylhexoside, were reduced, and we observed a local reduction in the lignin content in the anthers. Together, these results suggest that FvMYB46 controls fertility and efficient fruit set by regulating the cell wall structure, flavonoid biosynthesis, carbohydrate metabolism, and sugar and ROS signalling in flowers and early fruit development in F. vesca.